ANALYSIS OF FACTORS RELATED TO FARMERS’ BENEFITING FROM SAFFLOWER (Carthamus Tinctorius L.,) PRODUCTION SUPPORT: THE CASE OF CENTRAL ANATOLIA IN TURKEY - H. Yilmaz1; M. B. Comak; F. Turgut (Journal of Animal and Plant Sciences, 2016)
Despite the efforts of the government to increase oil seed production, Turkey continues to be import-dependent due to a net deficit in oilseeds and products. For this reason, The Turkish government began supporting oilseeds production in 2001 and continues to support oilseed production with production premium programs. The government of Turkey pays a premium per kilogram of oilseeds to producers. This study aims to analyze the factors related to farmers’ benefiting from oilseeds production support of safflower growers in the Central Anatolia region of Turkey. Data were collected by a questionnaire administered to 83 safflower growers selected by simple random sampling method. Chi-square test was used to analyze the existence of association between “benefiting or not” and each of the socio-economic variables. The result of the analyses showed that size of safflower cultivation area, state of dealing with livestock, agricultural credit use and practice of crop rotation are all important. Certainly, the potential of safflower production is tremendous in Turkey, but that potential can be obtained only through effective and more specific support policies. Safflower marketing and low price appears to be a major problem requiring attention in research area. For this reason, government should give support and guarantees on the marketing of safflower to increase the safflower production.
Keywords: Oilseed crops; Safflower Production; Support Policy; Turkey